Radio astronomy instrumentation for redshifted hydrogen line science - Price, DC (2013)
This thesis presents instrumentation with which to measure the abundance of neutral hydrogen gas in the Universe. Measuring where the Universe’s hydrogen is, and tracing how its distribution evolves with time, holds the key to understanding how galaxies evolve, the nature of dark energy, and how the first cosmic structures formed. In particular, this thesis looks at instrumentation for 21-cm intensity mapping telescopes. In 21-cm intensity mapping, the collective emission of many galaxies is measured, without individual detections. This technique promises to allow detection of the baryonic acoustic oscillation peaks in the power spectrum of the Universe’s matter distribution. Such a detection would increase constraints on cosmological parameters. There are two main approaches to designing a 21-cm intensity mapping instruments: using a filled aperture instrument such as a single-dish telescope, or using a sparse aperture instrument such as an interferometric array of dipoles. This thesis investigates analogue components for a sparse aperture instrument operating at 1.0-1.5 GHz. As part of this work, a 16-element sparse aperture array was designed and constructed. To test the array’s performance, field testing was conducted; the results of which are presented here. In addition to this, I have designed a new digital spectrometer for redshifted hydrogen line science, named HISPEC. A copy of this spectrometer has been installed on the Parkes 64 m telescope, as a digital signal processor for the 21-cm multibeam receiver. HISPEC has increased instantaneous bandwidth, higher interchannel isolation, and improved quantization efficiency as compared to the existing backend, MBCORR. The HISPEC equipped multibeam receiver is an ideal instrument for 21-cm intensity mapping at redshifts z<0.2.